2003
DOI: 10.1007/s00404-003-0525-6
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal outcome associated with oligohydramnios in uncomplicated term pregnancies

Abstract: In conclusion, in uncomplicated pregnancies at 40.0 to 41.6 weeks, oligohydramnios is independently associated with a higher risk of low birth weight centile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
78
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(95 citation statements)
references
References 10 publications
15
78
2
Order By: Relevance
“…Cesarean rate in the Oligohydramnios group was not significantly different from the control group, it's disharmonious with previous studies by Varma et al (9), and Locatelli et al (4). Similarly, cesarean rate in the SGA and Oligohydramnios group was not significantly different from the control group.…”
Section: Discussionsupporting
confidence: 50%
“…Cesarean rate in the Oligohydramnios group was not significantly different from the control group, it's disharmonious with previous studies by Varma et al (9), and Locatelli et al (4). Similarly, cesarean rate in the SGA and Oligohydramnios group was not significantly different from the control group.…”
Section: Discussionsupporting
confidence: 50%
“…Locatelli et al [10] reported that in uncomplicated term pregnancies with oligohydramnios, the presence of an AFI \ 5 independently increased the risk for a SGA infant. Morris et al [11] found that 60 % of babies were of LBW in the group with AFI \ 5, indicating that oligohydramnios had an association with growth restriction.…”
Section: Discussionmentioning
confidence: 99%
“…In this study 156 patients with gestational age from 30-40wks with Oligohydramnios AFI<5cms with intact membranes were analysed for perinatal outcome. 4 …”
Section: Methodsmentioning
confidence: 99%